Habent papam: volba papeže v českém celostátním tisku - Motal, Jan (Sacra, 2013)
The article aims to define a social framework used by Czech media for an interpretation of Vatican state, pope's office and catholicism. Based on a qualitative analyse of Czech news in print media during the papal vote in 2013 and involving an interpretation of the topics and values presented in the news, it argues that the social framework of catholicism in the Czech society is characterised by negative connotations. The Czech news viewed the pope and the church as a highly conservative, backward and morally corrupted institutions, constantly dealing with crimes. This picture is in the news supplemented with a perspective of protestantism. The study reveals that the Czech print media conforms to a negative attitude towards institutions.